Cerium-zirconium composite oxide doped at grain boundaries and surfaces, its manufacturing method and use

By doping rare earths and transition metals on the cerium-zirconium composite oxide particles and surfaces, the high-temperature stability and pore structure of cerium-zirconium composite oxides are enhanced, and the problem of degradation of catalyst performance in high-temperature environments is solved, purification efficiency is improved and precious metals is reduced.

JP2025502969AActive Publication Date: 2025-01-30GRIREM ADVANCED MATERIALS CO LTD +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024542093
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2023-02-13
Publication Date
2025-01-30
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

The performance of existing automotive exhaust and industrial exhaust gas purification catalysts deteriorates in high temperature and water vapor environments, and precious metal particles are prone to aggregation, resulting in the deactivation of the catalyst and it is difficult to effectively purify the exhaust gas.

Method used

The method of doping rare earth elements and transition metals on the cerium-zirconium composite oxide particles and surfaces is adopted to form cerium-zirconium composite oxides, enhancing their high temperature stability and pore structure, and inhibiting the aggregation of precious metal particles.

Benefits of technology

It improves the high temperature stability and catalytic efficiency of the catalyst, reduces the use of precious metals, and enhances the purification capacity of automobile exhaust, natural gas combustion and industrial organic waste gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502969000001_ABST
    Figure 2025502969000001_ABST
Patent Text Reader

Abstract

The present invention relates to a cerium-zirconium composite oxide doped on the grain boundary and surface, and its manufacturing method and use. The doping elements of the cerium-zirconium composite oxide are located partially or entirely on the grain boundary and surface, thereby increasing the number of defects and vacancies in the cerium-zirconium composite oxide, increasing the oxygen transfer ability, and providing good high-temperature stability. The cerium-zirconium composite oxide can inhibit the transfer, aggregation, and growth of precious metal particles, enhance the high-temperature stability of precious metal catalysts, and reduce the amount of precious metal used, and can be used in fields such as automobile exhaust gas purification, natural gas catalytic combustion, organic exhaust gas purification, and industrial flue gas denitrification treatment.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is filed based on a Chinese patent application with application number 202210135450.6 and filing date of February 14, 2022, and claims priority to the Chinese patent application, the entire contents of which are hereby incorporated by reference into this application.

[0002] The present invention relates to the technical field of cerium-zirconium composite oxides, and in particular to a cerium-zirconium composite oxide doped at the grain boundary and the surface, and a method for producing the same and uses thereof. [Background technology]

[0003] With the improvement of emission standards for automobile exhaust, industrial exhaust and smoke at home and abroad, the performance requirements for automobile exhaust purification catalysts and industrial exhaust and smoke treatment catalysts are also becoming higher. As a source of flowing pollution, automobiles are constantly changing the components and properties of exhaust gas during operation, and it is difficult to effectively purify automobile exhaust gas with ordinary catalysts. Therefore, automobile exhaust purification catalysts and motorcycle exhaust purification catalysts containing platinum, palladium and rhodium precious metals have been developed, and these catalysts use an important active coating material, namely cerium zirconium composite oxide. The cerium oxide in the cerium zirconium composite oxide has valence variability, and in an oxidizing or reducing atmosphere, it can be converted into Ce. 4+ and Ce 3+A reversible change of occurs, so that the cerium zirconium composite oxide has the function of storing and releasing oxygen, effectively widening the air-fuel ratio window of the catalyst, and greatly improving the catalytic performance of the automobile exhaust gas purification catalyst. The cerium zirconium composite oxide improves the dispersion degree of the precious metals supported on the catalyst and improves the utilization rate, so that the amount of precious metals used in the catalyst can be greatly reduced. The cerium zirconium composite oxide is an essential key material for automobile exhaust gas purification catalysts. The environment in which the automobile exhaust gas purification catalyst is placed is poor, and not only is the temperature high, but it can also reach 900°C or more in some cases, and it also contains a certain amount of water vapor, so the catalyst needs to have high temperature resistance, and the cerium zirconium composite oxide needs not only a high specific surface area, but also good high temperature stability performance. In addition, the cerium zirconium composite oxide also has the potential to be widely used in catalysts such as natural gas catalytic combustion, industrial organic exhaust gas treatment, and industrial flue gas denitrification.

[0004] The high temperature of automobile exhaust gas causes the structure of the cerium zirconium composite oxide to change, the specific surface area to decrease, and the performance to deteriorate, and it is necessary to improve the high temperature stability of the cerium zirconium composite oxide, especially in order to continue to improve and meet more stringent automobile exhaust gas emission standards. In addition, in the application of the cerium zirconium composite oxide to automobile exhaust gas purification catalysts, the platinum, palladium, and rhodium precious metal particles supported on the cerium zirconium composite oxide are easily moved, aggregated, and grown due to the degradation of high temperature exhaust gas for a long time, which causes the catalyst to be deactivated. Summary of the Invention [Problem to be solved by the invention]

[0005] Based on the above-mentioned situation of the prior art, the object of the present invention is to provide a cerium-zirconium composite oxide doped on the grain boundary and surface, and its preparation method and use, which improves the high-temperature stability of the cerium-zirconium composite oxide and increases oxygen vacancies, defects, etc., and the catalyst prepared by using the same is favorable for highly efficient support of precious metal particles, and inhibits the migration, aggregation and growth of precious metal particles, thereby improving the high-temperature stability performance of the catalyst. [Means for solving the problem]

[0006] In order to achieve the above object, a first aspect of the present invention provides a cerium zirconium composite oxide doped on grain boundaries and surfaces, the chemical formula of the cerium zirconium composite oxide being: x Zr 1-x-y M y O 2-α D δ where: M is the doping element of the cation, D is the doping element of the anion, 0.1≦x≦0.9, 0 <y≦0.2、0≦α≦0.1、0≦δ≦0.1である。

[0007] Furthermore, the grain boundaries and surface of the cerium-zirconium composite oxide contain one or more of an oxide of a doping element M, or an oxide of a doping element M and a nitrogen-containing compound formed by M and D, a fluoride, a phosphate, and a sulfate.

[0008] Furthermore, the doping element M is one or a combination of at least one of rare earth elements other than cerium, transition metal elements, alkaline earth metal elements, Al, and Si, and the doping element D is one or a combination of at least one of N, S, F, and P.

[0009] Furthermore, the rare earth element is one or a combination of one or more of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc, the transition metal element is one or a combination of one or more of Cu, Mn, Ni, Fe, Zn, Co, Ti, Hf, Cr, and W, and the alkaline earth metal element is one or a combination of one or more of Mg, Ca, Sr, and Ba.

[0010] Furthermore, the cationic doping element M comprises one or a combination of one or more of the following: La, Pr, Nd, Sm, Eu, Yb, Y, Sc, Cu, Mn, Hf, Fe, Co, Al, Si, Mg, Ba and Sr.

[0011] Furthermore, the cerium zirconium composite oxide has a specific surface area of ​​50 m after being kept at 1000°C for 10 hours. 2 / g, preferably 60m 2 / g, and the specific surface area after heating at 1100℃ for 4 hours is 35m 2 / g, preferably 40m 2 / g.

[0012] Furthermore, the total pore volume of the cerium zirconium composite oxide is greater than 0.4 mL / g, and the total pore volume after being kept at 1000° C. for 10 hours is greater than 0.2 mL / g.

[0013] Furthermore, the cerium zirconium composite oxide doped on the grain boundaries and surfaces has an element gradient distribution structure or a core-shell structure, and is preferably one or more of a structure in which the outer surface or shell is rich in cerium oxide, a structure in which the outer surface is rich in the doping element M, or a structure in which the doping element M is present on the outer surface and / or in the interior.

[0014] A second aspect of the present invention provides a method for producing the grain boundary and surface doped cerium zirconium composite oxide according to the first aspect of the present invention, Step S1: preparing aqueous solutions containing cerium ions and zirconium ions in a stoichiometric ratio required for the product, mixing them to obtain a mixed solution, subjecting the mixed solution to a one-stage or two-stage precipitation reaction with a basic substance in a reactor, filtering, washing, drying and roasting the resulting precipitate to obtain a cerium-zirconium-containing oxide; and step S2 of mixing the cerium-zirconium-containing oxide obtained in step S1 with liquid salts of doping elements M and D, drying the mixture, subjecting it to one or two heat treatments, and further subjecting it to one or two roastings to obtain a cerium-zirconium composite oxide doped at the grain boundaries and on the surface.

[0015] Furthermore, the aqueous solution containing zirconium ions in step S1 includes one or a combination of one or more aqueous solutions of zirconium oxychloride, zirconium oxynitrate, zirconium sulfate, zirconium acetate, and zirconium citrate.

[0016] Furthermore, the aqueous solution containing cerium ions in step S1 includes one or a combination of one or more aqueous solutions of cerium chloride, cerium nitrate, cerium sulfate, cerium acetate, and cerium citrate.

[0017] Furthermore, the basic substance includes at least one of magnesium hydrogen carbonate, urea, and hydroxide, carbonate, or hydrogen carbonate of at least one element of ammonium, sodium, and potassium, and is preferably at least one of sodium hydroxide, urea, ammonia water, and ammonium hydrogen carbonate.

[0018] Furthermore, the pH value during the precipitation process in step S1 is controlled to 4.5 to 14, preferably 5 to 11, the pH value at the end of the precipitation is controlled to 8 to 13, preferably 9 to 11, and the reaction temperature during the precipitation process is 0 to 120°C, preferably 20 to 80°C.

[0019] Furthermore, the liquid salts of the doping elements M include one or a combination of more than one of the following: chlorides, nitrates, sulfates, acetates, citrates, amino acid salts and molten salts or aqueous solutions of organosilicon compounds.

[0020] Furthermore, the doping element M is added in one or two steps in steps S1 and S2.

[0021] Furthermore, the doping element D is added in one or two steps in steps S1 and S2.

[0022] Furthermore, the doping element D is added in the form of one or a combination of one or more of the following: nitrates, fluorides, phosphates and sulfates.

[0023] Furthermore, the roasting temperature in step S1 is 500 to 1050° C. and the roasting time is 1 to 24 hours, and preferably, the roasting temperature is 600 to 950° C. and the roasting time is 3 to 12 hours.

[0024] Furthermore, the heat treatment temperature in step S2 is 100 to 600° C. and the time is 0.5 to 24 hours, and preferably, the heat treatment temperature is 150 to 450° C. and the time is 1 to 12 hours.

[0025] Furthermore, the roasting temperature in step S2 is 500 to 1050° C. and the roasting time is 1 to 24 hours, and preferably, the roasting temperature is 600 to 950° C. and the roasting time is 3 to 12 hours.

[0026] A third aspect of the present invention provides a catalyst prepared by employing the grain boundary and surface doped cerium zirconium composite oxide according to the first aspect of the present invention.

[0027] A fourth aspect of the present invention provides uses of the catalyst according to the third aspect of the present invention in the fields of automobile exhaust gas purification, natural gas catalytic combustion, organic exhaust gas purification and industrial flue gas denitrification treatment. Effect of the Invention

[0028] As described above, the present invention provides a cerium zirconium composite oxide doped on the grain boundary and surface, and its manufacturing method and use, in order to improve the high temperature stability and catalytic application effect of the cerium zirconium composite oxide. The grain boundary and surface of the cerium zirconium composite oxide provided by the present invention contain an oxide of doping element M, or an oxide of doping element M and a nitrogen-containing compound formed by M and D, fluoride, phosphate, sulfate, etc., and the doping element M, or M and D, are located on the grain boundary and surface of the cerium zirconium composite oxide. The interaction between the doping element and the crystal grains of the cerium zirconium composite oxide is enhanced, and the dopant at the grain boundary plays the role of dispersing and covering the cerium zirconium crystal grains, so that the cerium zirconium composite oxide has good high temperature stability performance, and at the same time, the number of defects and vacancies of the cerium zirconium composite oxide is increased, and the oxygen transfer ability is enhanced, which can effectively improve the catalytic activity of the catalyst and reduce the amount of precious metal used in the catalyst. In addition, the cerium-zirconium composite oxide can inhibit the migration, aggregation and growth of precious metal particles, and enhance the high-temperature stability performance of precious metal catalysts, and can be used in fields such as automobile exhaust gas purification, natural gas catalytic combustion, organic exhaust gas purification and industrial flue gas denitrification treatment.

[0029] The present invention has the following beneficial technical effects over the prior art: (1) The cerium zirconium composite oxide doped on the grain boundaries and surface provided in the embodiments of the present invention contains an oxide of a doping element M, or an oxide of a doping element M and a nitrogen-containing compound formed by M and D, a fluoride, a phosphate, a sulfate, etc., on its grain boundaries and surface, and the doping element M, or M and D, are located on the grain boundaries and surface of the cerium zirconium composite oxide. The cerium zirconium composite oxide has abundant defects and vacancies, and the defects located on the grain boundaries are particularly abundant, so that the interaction between the doping element and the crystal grains is enhanced, and the dopant located on the grain boundaries acts to disperse and cover the cerium zirconium crystal grains, thereby improving the high temperature stability performance of the cerium zirconium composite oxide. (2) The cerium zirconium composite oxide doped at the grain boundaries and surface provided in the embodiments of the present invention is doped at the grain boundaries and surface, especially at the grain boundaries, to allow the cerium zirconium composite oxide to have abundant crystal grain defects, thereby improving the activity of the dopant and improving the effective utilization rate of the dopant, and promoting the catalytic action of the dopant. (3) The catalyst produced by applying the cerium-zirconium composite oxide doped on the grain boundaries and surface of the present invention to support precious metals such as platinum, palladium, and rhodium is advantageous in terms of efficient dispersion and support of precious metal catalyst particles such as platinum, palladium, and rhodium compared to conventional cerium-zirconium composite oxides, since the cerium-zirconium composite oxide has a large number of defects, and has high activity and abundant defect sites for the dopant, and is effective in improving the catalytic activity of the catalyst and reducing the amount of precious metal used in the catalyst, etc. In addition, the precious metal particles preferentially bond with the dopant on the grain boundaries, and there is a strong interaction between the two, which suppresses the movement, aggregation, growth, etc. of precious metal catalyst particles at high temperatures, improving the high-temperature stability performance of the catalyst. [Brief description of the drawings]

[0030] [Figure 1] 1 is a flow chart of a method for producing a grain boundary and surface doped cerium zirconium composite oxide of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are merely illustrative and do not limit the scope of the present invention. Furthermore, in the following description, descriptions of known structures and techniques are omitted to avoid unnecessary confusion of the concept of the present invention.

[0032] The first aspect of the present invention provides a cerium zirconium composite oxide doped at grain boundaries and surfaces, and the chemical formula of the cerium zirconium composite oxide is Ce x Zr 1-x-y M y O 2-α D δ wherein M is a cation doping element and D is an anion doping element, 0.1 ≦ x ≦ 0.9, 0 < y ≦ 0.2, 0 ≦ α ≦ 0.1, 0 ≦ δ ≦ 0.1, and preferably, 0.01 ≦ δ ≦ 0.08.

[0033] The grain boundaries and surfaces of the cerium zirconium composite oxide contain one or more of an oxide of the doping element M, or a nitrogen-containing compound, fluoride, phosphate, and sulfate formed by the oxide of the doping element M and M and D. The doping element M, or M and D, is located at the grain boundaries and surfaces of the cerium zirconium composite oxide, and the existing form is one or more of an oxide, a nitrogen-containing compound, a fluoride, a phosphate, and a sulfate.

[0034] Generally, by doping at grain boundaries and surfaces, one or more of an oxide of the doping element M, or a nitrogen-containing compound, fluoride, phosphate, and sulfate formed by the oxide of the doping element M and M and D can be contained in the grain boundaries and surfaces of the cerium zirconium composite oxide. Further, the doping element M, or M and D, is located at the grain boundaries and surfaces of the cerium zirconium composite oxide, and the existing form is one or more of an oxide, a nitrogen-containing compound, a fluoride, a phosphate, and a sulfate. Further, the M element contains at least one of La, Pr, Nd, Y, Sc, Cu, Mn, Hf, Mg, Ba, and Sr at the grain boundaries and surfaces of the cerium zirconium composite oxide, and the molar occupancy of the M element at the grain boundaries and surfaces is 10% - 70%. The D element is preferably at least one of N and S at the grain boundaries and surfaces, and the molar occupancy of the D element at the grain boundaries and surfaces is 10% - 70%. By controlling precipitation parameters, the heat treatment temperature and roasting temperature, time, atmosphere, etc. of the product, the form and ratio of M and D at the grain boundaries and surfaces are adjusted and controlled.

[0035] By realizing the doping at the grain boundaries and surface of the cerium-zirconium composite oxide, the oxide has abundant defects and vacancies, especially the defects located at the grain boundaries are more abundant, which enhances the interaction between the doping element and the crystal grains, and the dopant located at the grain boundaries plays the role of dispersing and coating the cerium-zirconium crystal grains, thereby improving the high temperature stability performance of the cerium-zirconium composite oxide.

[0036] The doping element M is converted to an oxide at the grain boundary, on the surface and within the crystal grain, or M is combined with D to form one or more of a nitrogen-containing compound, a fluoride, a phosphate and a sulfate. Preferably, the doping element M is converted to an oxide at the grain boundary and on the surface of the cerium-zirconium composite oxide, or / and M is combined with D to form one or more of a nitrogen-containing compound, a fluoride, a phosphate and a sulfate, and M forms an oxide and D is combined with M to form a nitrogen-containing compound, a fluoride, a phosphate, a sulfate, etc., thereby improving the high-temperature stability performance of the cerium-zirconium composite oxide and adjusting and controlling the pore structure or the oxygen storage capacity, etc.

[0037] The doping element M may be one or more of a rare earth element other than cerium, a transition metal element, an alkaline earth metal element, and Al, Si, where the rare earth element may be one or more of a combination of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc, preferably one or more of La, Pr, Nd, Sm, Eu, Yb, Y, and Sc; The transition metal element may be one or a combination of more than one of Cu, Mn, Ni, Fe, Zn, Co, Ti, Hf, Cr and W, the alkaline earth metal element may be one or a combination of more than one of Mg, Ca, Sr and Ba, more preferably the doping element M of the cation comprises one or a combination of more than one of La, Pr, Nd, Sm, Eu, Yb, Y, Sc, Cu, Mn, Hf, Fe, Co, Al, Si, Mg, Ba, Sr. The doping element D may be one or a combination of more than one of N, S, F, P, preferably N, S.

[0038] The cerium-zirconium composite oxide has a specific surface area of ​​50m2 after being heated at 1000°C for 10 hours. 2 / g, preferably 60m 2 / g, and the specific surface area after heating for 4 hours at 1100°C is 35m 2 / g, preferably 40m 2 Further, the total pore volume of the cerium zirconium composite oxide is greater than 0.4 mL / g, and the total pore volume after being kept at 1000° C. for 10 hours is greater than 0.2 mL / g.

[0039] Furthermore, the cerium zirconium composite oxide doped on the grain boundary and surface includes an element gradient distribution structure or a core-shell structure, preferably one or more of the following: an outer surface or shell is rich in cerium oxide, or an outer surface is rich in doping element M, or an outer surface is rich in doping element M, which is on the outer surface or / and inside. This further improves the high temperature stability performance and oxygen storage capacity of the cerium zirconium composite oxide, and is favorable for dispersing and supporting precious metal particles, improving catalytic activity and reducing the amount of precious metal used. For other features and advantages of the element gradient distribution structure of the cerium zirconium composite oxide, please refer to the Chinese patent application with application number CN202010982979.2, filed on September 17, 2020, entitled "Cerium zirconium composite oxide with element gradient distribution and its manufacturing method" and its full content description. For other features and advantages of the core-shell structure of cerium-zirconium composite oxide, please refer to the Chinese patent application with application number CN202010982980.5, filed on September 17, 2020, and title of the invention "Core-shell structured cerium-zirconium composite oxide and its manufacturing method" and its full content description.

[0040] The second aspect of the present invention provides a method for producing the grain boundary and surface doped cerium zirconium composite oxide according to the first aspect of the present invention, the flow chart of which is shown in FIG. 1 , Step S1: preparing aqueous solutions containing cerium ions and zirconium ions in a stoichiometric ratio required for the product, mixing them to obtain a mixed solution, subjecting the mixed solution to a one-stage or two-stage precipitation reaction with a basic substance in a reactor, filtering, washing, drying and roasting the resulting precipitate to obtain a cerium-zirconium-containing oxide; and step S2 of mixing the cerium-zirconium-containing oxide obtained in step S1 with liquid salts of doping elements M and D, drying the mixture, subjecting it to one or two heat treatments, and further subjecting it to one or two roastings to obtain a cerium-zirconium composite oxide doped at the grain boundaries and on the surface.

[0041] Here, the aqueous solution containing zirconium ions in step S1 may be one or a combination of one or more aqueous solutions of zirconium oxychloride, zirconium oxynitrate, zirconium sulfate, zirconium acetate, and zirconium citrate, the aqueous solution containing cerium ions may be one or a combination of one or more aqueous solutions of cerium chloride, cerium nitrate, cerium sulfate, cerium acetate, and cerium citrate, and the basic substance may be at least one of magnesium hydrogen carbonate, urea, and hydroxide, carbonate, or hydrogen carbonate of at least one element of ammonium, sodium, and potassium, and is preferably at least one of sodium hydroxide, urea, ammonia water, and ammonium hydrogen carbonate. The pH value during the precipitation process in step S1 is controlled to 4.5 to 14, preferably 5 to 11, the pH value at the end of precipitation is controlled to 8 to 13, preferably 9 to 11, the reaction temperature during the precipitation is 0 to 120°C, preferably 20 to 80°C, the roasting temperature in step S1 is 500 to 1050°C, and the time is 1 to 24 hours, preferably the roasting temperature is 600 to 950°C, and the time is 3 to 12 hours.

[0042] The doping element M may be added in one or two steps in steps S1 and S2. For example, the doping element M may be added alone in step S1 or S2 according to the stoichiometry required for the product, or a part of the doping element M may be added in step S1 and another part in step S2 according to the stoichiometry required for the product, and any of the above addition methods may be selected according to actual needs. The molar occupancy rate of the M element in the grain boundary and surface of the cerium-zirconium composite oxide is 10-70 mol%. The liquid salt of the doping element M may include one or a combination of one or more of chlorides, nitrates, sulfates, acetates, citrates, amino acid salts, and molten salts or aqueous solutions of organosilicon compounds.

[0043] The doping element D may be added in one or two steps in steps S1 and S2, and either addition method may be selected according to actual needs, similar to the addition method of the doping element M. The molar occupancy rate of the D element in the grain boundary and surface of the cerium-zirconium composite oxide is 10 to 70 mol %. The doping element D may be added in the form of one or a combination of one or more of nitrates, fluorides, phosphates, and sulfates.

[0044] The heat treatment temperature in step S2 is 100-600°C, and the time is 0.5-24h, preferably, the heat treatment temperature is 150-450°C, and the time is 1-12h. In addition, different heat treatment regimes can be adopted, for example, heat treatment is performed stepwise to make the doping element penetrate more, more uniformly and stably into the grain boundaries and surfaces.

[0045] In step S2, the roasting temperature is 500-1050°C and the roasting time is 1-24h, preferably, the roasting temperature is 600-950°C and the roasting time is 3-12h. Two roasting steps can also be adopted, which effectively controls the particle size and dispersibility of the cerium zirconium composite oxide and further improves its high temperature stability.

[0046] In the present invention, the doping of the doping element M and the doping element D in the grain boundary and the surface of the cerium-zirconium composite oxide can be obtained by mixing M and D in the form of an ionic solution or liquid salt with the cerium-zirconium-containing oxide in solid-liquid form in step S2, and then drying and further heat-treating and roasting the mixture, or by adding M and D in the form of an ionic solution or liquid salt in two steps of step S1 and step S2.

[0047] The third aspect of the present invention provides a catalyst prepared by using the cerium-zirconium composite oxide doped on the grain boundary and surface as described in the first aspect of the present invention, which can be applied in the fields of automobile exhaust gas purification, natural gas catalytic combustion, organic exhaust gas purification and industrial flue gas denitrification treatment.

[0048] A fourth aspect of the present invention provides uses of the catalyst according to the third aspect of the present invention in the fields of automobile exhaust gas purification, natural gas catalytic combustion, organic exhaust gas purification and industrial flue gas denitrification treatment.

[0049] The present invention will now be further described with reference to specific examples.

[0050] Comparative Example 1 Molar distribution of cerium-zirconium oxide: Ce 0.50 Zr 0.35 La 0.10 Y 0.05 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 , LaCl 3 , Y.C.L. 3 The mixture was mixed with 2.5 mol / L sodium hydroxide solution to cause a precipitation reaction, the precipitation temperature was 25°C, the pH value during the precipitation process was controlled to 10±0.2, and the pH value at the end of the precipitation was 11. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 800°C for 5 hours to obtain a cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.353 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.161 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 47.6 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 31.5 m 2 / g.

[0051] Comparative Example 2 Molar distribution of cerium-zirconium oxide: Ce 0.80 Zr 0.10 La 0.05 Nd 0.05 O 1.97 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 )2 , La(NO 3 ) 3 , Nd(NO 3 ) 3 The mixture was mixed with 2.5 mol / L aqueous ammonia solution to cause a precipitation reaction, the precipitation temperature was 25°C, the pH value during the precipitation process was 10±0.2, and the pH value at the end of the precipitation was 11. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 800°C for 5 hours to obtain a cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.306 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.148 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 44.7 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 30.9 m 2 / g.

[0052] Example 1 Molar distribution of cerium-zirconium oxide: Ce 0.50 Zr 0.35 La 0.10 Y 0.05 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out a precipitation reaction, the precipitation temperature is 25°C, the pH value during the precipitation is controlled to 10±0.2, and the pH value at the end of the precipitation is 11. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 800°C for 5 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.50 Zr 0.35 La 0.10 Y 0.05 O 1.98 The total metal ion concentration of La(NO 3 ) 3, Y(NO 3 ) 3 The mixed solution was prepared by mixing a certain volume of La(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 200°C for 2 hours, and then roasted at 600°C for 5 hours to obtain a cerium-zirconium composite oxide, in which La and Y were both located in the form of oxides at the grain boundaries and on the surface. The cerium-zirconium composite oxide had a total pore volume of 0.458 mL / g, and after high-temperature aging at 1000°C for 10 hours, the total pore volume was 0.230 mL / g. The cerium-zirconium composite oxide had a specific surface area of ​​53.2 m after high-temperature aging at 1000°C for 10 hours. 2 / g, and the specific surface area after high-temperature aging at 1100°C for 4 hours is 36.4 m 2 / g.

[0053] Example 2 Molar distribution of cerium-zirconium oxide: Ce 0.80 Zr 0.10 La 0.05 Nd 0.05 O 1.97 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture is mixed with 2.5 mol / L aqueous ammonia solution to carry out precipitation reaction, the precipitation temperature is 25°C, the pH value during the precipitation is controlled to 10±0.2, and the pH value at the end of the precipitation is 11. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 800°C for 5 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.80 Zr 0.10 La 0.05 Nd 0.05 O 1.97 The total metal ion concentration of La(NO 3 ) 3, Nd(NO 3 ) 3 The mixed solution was prepared by mixing a certain volume of La(NO 3 ) 3 , Nd(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 300°C for 1 hour, and then roasted at 800°C for 3 hours to obtain a cerium-zirconium composite oxide, in which La and Nd were located in the form of oxides on the grain boundaries and surface. The total pore volume of the cerium-zirconium composite oxide was 0.423 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.209 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 50.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 35.6 m 2 / g.

[0054] Example 3 Molar distribution of cerium-zirconium oxide: Ce 0.40 Zr 0.50 La 0.05 Nd 0.05 O 1.96 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture is mixed with 2.5 mol / L aqueous ammonia solution to carry out precipitation reaction, the precipitation temperature is 45°C, the pH value during the precipitation is controlled to 6±0.2, and the pH value at the end of the precipitation is 9.5. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 800°C for 5 hours to obtain a cerium-zirconium-containing oxide. The molar distribution of cerium-zirconium composite oxide with a total metal ion concentration of 2.5 mol / L La(NO 3 ) 3 , Nd(NO 3 ) 3 The mixed solution was prepared by mixing a certain volume of La(NO 3 ) 3, Nd(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 300°C for 5 hours, and then roasted at 800°C for 3 hours to obtain a cerium-zirconium composite oxide, in which La and Nd were located in the form of oxides on the grain boundaries and surface. The total pore volume of the cerium-zirconium composite oxide was 0.433 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.229 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 53.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 36.6 m 2 / g.

[0055] Example 4 Molar distribution of cerium-zirconium oxide: Ce 0.25 Zr 0.65 La 0.05 Y 0.05 O 1.97 The total metal ion molar concentration of Ce(NO 3 ) 3 , La(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture is mixed with 2.5 mol / L aqueous ammonia solution to carry out precipitation reaction, the precipitation temperature is 55°C, the pH value during the precipitation is controlled to 6±0.2, and the pH value at the end of the precipitation is 9.5. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 750°C for 5 hours to obtain lanthanum-containing cerium zirconium oxide. The molar distribution of cerium-zirconium oxide is 2.5 mol / L Y(NO 3 ) 3 The solution was mixed at a constant volume and Y(NO 3 ) 3The solution was uniformly mixed with the lanthanum-containing cerium zirconium oxide obtained above, dried, heat-treated at 500°C for 5 hours, and then roasted at 850°C for 3 hours to obtain a cerium zirconium composite oxide, in which Y was located in the form of oxide on the grain boundaries and surface. The total pore volume of the cerium zirconium composite oxide was 0.401 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.201 mL / g. The specific surface area of ​​the cerium zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 50.1 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 35.1 m 2 / g.

[0056] Example 5 Molar distribution of cerium-zirconium oxide: Ce 0.80 Zr 0.05 Nd 0.15 O 1.95 S 0.05 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 Mix 250mL of the mixture, add 1.0mol / L sulfuric acid solution as a coordinating agent, add S and mix uniformly, mix the mixture with 2.5mol / L sodium hydroxide solution to carry out precipitation reaction, precipitation temperature is 25℃, pH value during precipitation is 10-14, and pH value at the end of precipitation is 12, and the precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is dried at 110℃ for 10 hours and roasted at 500℃ for 10 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.80 Z r0.05 Nd 0.15 O 1.95 S 0.05 The molar distribution is 1.50 mol / L Nd(NO 3 ) 3 Solution and 0.4mol / L (NH 4 ) 2 SO 4 The solution was prepared by mixing a fixed volume. Nd(NO 3 ) 3 solution, (NH 4 )2 SO 4 The solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above in a stepwise manner, dried, heat-treated at 200°C for 24 hours, and then roasted at 600°C for 6 hours to obtain a cerium-zirconium composite oxide, containing elements Nd and S on its grain boundaries and surface, respectively in the form of neodymium oxide and neodymium sulfate. The total pore volume of the cerium-zirconium composite oxide was 0.402 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.204 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 50.2 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 35.1 m 2 / g.

[0057] Example 6 Molar distribution of cerium-zirconium oxide: Ce 0.40 Zr 0.40 La 0.05 Nd 0.10 Y 0.05 O 1.96 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 , La(NO 3 ) 3 The mixture was mixed with 2.4 mol / L ammonium bicarbonate solution to carry out a precipitation reaction, the precipitation temperature was 30°C, the pH value during the precipitation was 7±0.2, and the pH value at the end of the precipitation was 8. The precipitate was filtered, washed and other post-treatments were carried out to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 500°C for 24 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.40 Zr 0.40 La 0.05 Nd 0.10 Y 0.05 O 1.96 The molar distribution of Nd(NO 3 ) 3, Y(NO 3 ) 3 The mixed solution was prepared by mixing a certain volume and Nd(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 300°C for 12 hours, and then roasted at 800°C for 12 hours to obtain a cerium-zirconium composite oxide, containing the elements Nd and Y on the grain boundaries and surface, both of which existed in the form of oxides. The total pore volume of the cerium-zirconium composite oxide was 0.462 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.236 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 54.6 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 36.8 m 2 / g.

[0058] Example 7 Molar distribution of cerium-zirconium oxide: Ce 0.40 Zr 0.50 La 0.10 O 1.95 P 0.05 CeCl with a total metal ion molar concentration of 1.3 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.2 mol / L sodium carbonate solution to carry out precipitation reaction, the precipitation temperature is 50°C, the pH value during the precipitation is controlled to 9±0.2, and the pH value at the end of the precipitation is 10. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 600°C for 8 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.40 Zr 0.50 La 0.10 O 1.95 P 0.05 The molar distribution of La(NO) is 1.0 mol / L. 3 ) 3A fixed volume of La(NO 3 ) 3 The cerium-zirconium composite oxide obtained above was uniformly mixed with the cerium-zirconium-containing oxide obtained above in a stepwise manner, and after drying, the mixture was heat-treated at 400°C for 6 hours and then roasted at 800°C for 8 hours to obtain a cerium-zirconium composite oxide. La was present in the form of oxide and phosphate at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.468 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.240 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 55.1 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 37.2 m 2 / g.

[0059] Example 8 Molar distribution of cerium-zirconium oxide: Ce 0.333 Zr 0.581 La 0.044 Pr 0.042 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out precipitation reaction, the precipitation temperature is 60°C, the pH value during the precipitation is controlled to 10±0.2, and the pH value at the end of the precipitation is 11. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 750°C for 6 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.333 Zr 0.581 La 0.044 Pr 0.042 O 1.98 The molar distribution of La(NO) with a total metal ion concentration of 1.0 mol / L 3 ) 3 , Pr(NO 3 ) 3A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Pr(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 300°C for 6 hours, and then roasted at 800°C for 6 hours to obtain a cerium-zirconium composite oxide, in which La and Pr existed in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.523 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.259 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 56.9 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 40.2 m 2 / g.

[0060] Example 9 Molar distribution of cerium-zirconium oxide: Ce 0.373 Zr 0.520 La 0.044 Y 0.063 O 1.98 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 , La(NO 3 ) 3 A mixture of 250 mL of La (50% of the total amount of La required) was mixed and prepared, and the mixture was mixed with 3.0 mol / L aqueous ammonia solution to cause a precipitation reaction. The precipitation temperature was 30°C, the pH value during the precipitation was 9-12, and the pH value at the end of the precipitation was 9. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor. The precursor was then dried at 110°C for 10 hours and roasted at 700°C for 8 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.373 Zr 0.520 La 0.044 Y 0.063 O 1.98 The molar distribution of La(NO) with a total metal ion concentration of 1.0 mol / L3 ) 3 (50% of the total amount of La required), Y(NO 3 ) 3 A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 350°C for 6 hours, and then roasted at 700°C for 8 hours to obtain a cerium-zirconium composite oxide, in which La and Y were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.491 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.248 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 55.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 37.9 m 2 / g.

[0061] Example 10 Molar distribution of cerium-zirconium oxide: Ce 0.55 Zr 0.25 La 0.15 Cu 0.05 O 1.95 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture was mixed with 2.2 mol / L urea solution, then added to an autoclave, gradually heated to 120°C, and hydrothermally reacted for 8 hours. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 800°C for 5 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.55 Zr 0.25 La 0.15 Cu 0.05 O 1.95 The total metal ion concentration of La(NO3 ) 3 , Cu(NO 3 ) 2 A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Cu(NO 3 ) 2 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 600°C for 0.5 hours, and roasted at 1050°C for 1 hour to obtain a cerium-zirconium composite oxide, in which La and Cu existed in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.443 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.219 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 51.7 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 35.8 m 2 / g.

[0062] Example 11 Molar distribution of cerium-zirconium oxide: Ce 0.50 Zr 0.35 Ba 0.05 Mn 0.10 O 1.96 CeCl with a total metal ion molar concentration of 1.2 mol / L 3 , ZrOCl 2 The mixture was mixed with 2.1 mol / L sodium hydroxide solution to cause a precipitation reaction, the precipitation temperature was 90°C, the pH value during the precipitation was 12-14, and the pH value at the end of the precipitation was 13. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 1050°C for 1 hour to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.50 Zr 0.35 Ba 0.05 Mn 0.10 O 1.96 The total metal ion concentration of Ba(NO 3 )2 , Mn(NO 3 ) 2 A fixed volume of the mixed solution was prepared and Ba(NO 3 ) 2 , Mn(NO 3 ) 2 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 400°C for 6 hours, and then roasted at 700°C for 8 hours to obtain a cerium-zirconium composite oxide, in which Ba and Mn existed in the form of oxides on the grain boundaries and surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.451 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.224 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 52.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 36.2 m 2 / g.

[0063] Example 12 Molar distribution of cerium-zirconium oxide: Ce 0.330 Zr 0.580 La 0.033 Nd 0.032 Y 0.025 O 1.97 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 , LaCl 3 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out precipitation reaction, the precipitation temperature is 45°C, the pH value during the precipitation is controlled to 10±0.2, and the pH value at the end of the precipitation is 11. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 850°C for 5 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.330 Zr 0.580 La 0.033 Nd 0.032 Y 0.025 O 1.97The molar distribution of Nd(NO 3 ) 3 , Y(NO 3 ) 3 A fixed volume of mixed solution was prepared and Nd(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 350°C for 6 hours, and then roasted at 850°C for 5 hours to obtain a cerium-zirconium composite oxide. The grain boundaries and surfaces of the cerium-zirconium composite oxide contained Nd and Y elements, both of which existed in the form of oxides. The total pore volume of the cerium-zirconium composite oxide was 0.548 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.276 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 57.1 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 40.9 m 2 / g.

[0064] Example 13 Molar distribution of cerium-zirconium oxide: Ce 0.18 Zr 0.64 La 0.03 Y 0.15 O 1.96 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 , Y.C.L. 3 The mixture was mixed with 2.5 mol / L sodium hydroxide solution to cause a precipitation reaction, the precipitation temperature was 50°C, the pH value during the precipitation was 10-14, and the pH value at the end of the precipitation was 10.5. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 650°C for 8 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.18 Zr 0.64 La 0.03 Y 0.15 O1.96 With a molar distribution of 0.5 mol / L La(NO 3 ) 3 The solution was mixed at a constant volume and La(NO 3 ) 3 The solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 200°C for 10 hours, and then roasted at 650°C for 8 hours to obtain a cerium-zirconium composite oxide, in which La was present in the form of an oxide at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.582 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.286 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 57.9 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 43.8 m 2 / g.

[0065] Example 14 Molar distribution of cerium-zirconium oxide: Ce 0.16 Zr 0.78 La 0.02 Nd 0.04 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 The mixture was mixed with 2.5 mol / L sodium hydroxide solution to cause a precipitation reaction, the precipitation temperature was 80°C, the pH value during the precipitation was 10-14, and the pH value at the end of the precipitation was 10. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 600°C for 10 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.16 Zr 0.78 La 0.02 Nd 0.04 O 1.98 The total metal ion concentration of La(NO 3 ) 3 , Nd(NO 3 ) 3A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Nd(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 400°C for 6 hours, and then roasted at 600°C for 12 hours to obtain a cerium-zirconium composite oxide, in which La and Nd were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.591 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.289 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 60.2 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 45.1 m 2 / g.

[0066] Example 15 Molar distribution of cerium-zirconium oxide: Ce 0.40 Zr 0.40 Al 0.20 O 1.93 N 0.08 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture was mixed with 2.2 mol / L ammonia water / ammonium bicarbonate mixed solution to carry out a precipitation reaction, the precipitation temperature was 30°C, the pH value during the precipitation was 7.5-8.5, and the pH value at the end of the precipitation was 8. The precipitate was filtered, washed, and other post-treatments were carried out to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 950°C for 4 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.40 Zr 0.40 Al 0.20 O 1.93 N 0.08 The molar distribution is 2.2 mol / L Al(NO 3 ) 3 solution and 0.8 mol / L NH4 NO 3 The solution was mixed at a constant volume and Al(NO 3 ) 3 solution, NH 4 NO 3 The solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above in a stepwise manner, dried, heat-treated at 300°C for 8 hours, and then roasted at 800°C for 6 hours to obtain a cerium-zirconium composite oxide, in which Al was present in the form of oxide at the grain boundaries and on the surface of the cerium-zirconium composite oxide, and N was present in the form of a nitrogen-containing compound at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.611 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.301 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 62.4 m 2 / g, and the specific surface area after high-temperature aging at 1100°C for 4 hours is 46.3 m 2 / g.

[0067] (Example 16) Molar distribution of cerium-zirconium oxide: Ce 0.60 Zr 0.30 Ba 0.10 O 1.98 F 0.01 CeCl with a total metal ion molar concentration of 1.0 mol / L 3 , ZrOCl 2 The mixture was mixed with 2.3 mol / L sodium hydroxide solution to cause a precipitation reaction, the precipitation temperature was 20°C, the pH value during the precipitation was 4.5-10, and the pH value at the end of the precipitation was 11. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 700°C for 8 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.60 Zr 0.30 Ba 0.10 O 1.98 F 0.01 Molar distribution of 1.0 mol / L Ba(NO 3 ) 2Solution and 0.1 mol / L NH 4 F solution was mixed and prepared at a fixed volume, and Ba(NO 3 ) 2 solution, NH 4 The F solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above in a sequential stepwise manner, dried, heat-treated at 150°C for 12 hours, and then roasted at 600°C for 12 hours to obtain a cerium-zirconium composite oxide, in which Ba was present in the form of oxide at the grain boundaries and on the surface of the cerium-zirconium composite oxide, and F was present in the form of fluoride at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.450 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.222 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 52.2 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 36.2 m 2 / g.

[0068] (Example 17) Molar distribution of cerium-zirconium oxide: Ce 0.45 Zr 0.35 Y 0.15 Mg 0.05 O 1.96 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 , Y(NO 3 ) 3 The mixture was mixed with 3.0 mol / L aqueous ammonia solution to cause a precipitation reaction, the precipitation temperature was 30°C, the pH value during the precipitation was 9-12, and the pH value at the end of the precipitation was 9. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 950°C for 3 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.45 Zr 0.35 Y 0.15 Mg 0.05 O 1.96The molar distribution of 0.5 mol / L of Mg(NO 3 ) 2 The solution was mixed at a constant volume and Mg(NO 3 ) 2 The solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 250°C for 10 hours, and then roasted at 900°C for 5 hours to obtain a cerium-zirconium composite oxide, in which Mg element was present in the form of oxide on the grain boundaries and surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.438 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.221 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 52.9 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 36.1 m 2 / g.

[0069] (Example 18) Molar distribution of cerium-zirconium oxide: Ce 0.40 Zr 0.45 Pr 0.10 Sm 0.05 O 1.97 CeCl with a total metal ion molar concentration of 0.8 mol / L 3 , ZrOCl 2 The mixture was mixed with 1.0 mol / L sodium hydroxide solution to cause a precipitation reaction, the precipitation temperature was 50°C, the pH value during the precipitation was 5-9, and the pH value at the end of the precipitation was 10. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 500°C for 16 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.40 Zr 0.45 Pr 0.10 Sm 0.05 O 1.97 The total metal ion concentration of Pr(NO 3 ) 3 , Sm(NO 3 ) 3A fixed volume of mixed solution was prepared and Pr(NO 3 ) 3 , Sm(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 300°C for 8 hours, and then roasted at 500°C for 24 hours to obtain a cerium-zirconium composite oxide, in which Pr and Sm elements existed in the form of oxides on the grain boundaries and surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.451 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.235 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 54.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 36.9 m 2 / g.

[0070] (Example 19) Molar distribution of cerium-zirconium oxide: Ce 0.20 Zr 0.60 EU 0.10 Co 0.10 O 1.98 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture was mixed with 3.0 mol / L aqueous ammonia solution to cause a precipitation reaction, the precipitation temperature was 35°C, the pH value during the precipitation was 9-12, and the pH value at the end of the precipitation was 9. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 600°C for 12 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.20 Zr 0.60 EU 0.10 Co 0.10 O 1.98 The molar distribution of Eu(NO) with a total metal ion concentration of 2.2 mol / L 3 ) 3 , Co(NO 3 )2 A fixed volume of the mixed solution was prepared and Eu(NO 3 ) 3 , Co(NO 3 ) 2 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 450°C for 1 hour, and then roasted at 800°C for 6 hours to obtain a cerium-zirconium composite oxide, in which Eu and Co elements were both present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.552 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.279 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 57.3 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 42.5 m 2 / g.

[0071] (Example 20) Molar distribution of cerium-zirconium oxide: Ce 0.90 Zr 0.05 Gd 0.03 Yb 0.02 O 1.97 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture was mixed with 3.0 mol / L aqueous ammonia solution to cause a precipitation reaction, the precipitation temperature was 20°C, the pH value during the precipitation was 9-12, and the pH value at the end of the precipitation was 9. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 550°C for 12 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.90 Zr 0.05 Gd 0.03 Yb 0.02 O 1.97 The molar distribution of Gd(NO 3 ) 3 , Yb(NO3 ) 3 A fixed volume of the mixed solution was prepared and Gd(NO 3 ) 3 , Yb(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 350°C for 7 hours, and then roasted at 600°C for 12 hours to obtain a cerium-zirconium composite oxide, containing Gd and Yb elements at the grain boundaries and on the surface, both of which existed in the form of oxides. The total pore volume of the cerium-zirconium composite oxide was 0.406 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.210 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 50.4 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 35.3 m 2 / g.

[0072] Example 21 Molar distribution of cerium-zirconium oxide: Ce 0.70 Zr 0.20 Fe 0.04 Ba 0.04 Sc 0.02 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 The mixture was mixed with 2.5 mol / L sodium hydroxide solution to cause a precipitation reaction, the precipitation temperature was 80°C, the pH value during the precipitation was 10-14, and the pH value at the end of the precipitation was 10. The precipitate was filtered, washed, and other post-treatments were performed to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 600°C for 12 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.70 Zr 0.20 Fe 0.04 Ba 0.04 Sc 0.02 O 1.98 The molar distribution of Fe(NO) with a total metal ion concentration of 1.1 mol / L 3 ) 3, Ba(NO 3 ) 2 and Sc(NO 3 ) 3 A fixed volume of the mixed solution was prepared and Fe(NO 3 ) 3 , Ba(NO 3 ) 2 , Sc(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 300°C for 8 hours, and then roasted at 800°C for 7 hours to obtain a cerium-zirconium composite oxide, containing Fe, Ba, and Sc elements at the grain boundaries and on the surface, all of which existed in the form of oxides. The cerium-zirconium composite oxide had a total pore volume of 0.431 mL / g, and a total pore volume of 0.217 mL / g after high-temperature aging at 1000°C for 10 hours. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 51.6 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 35.7 m 2 / g.

[0073] Example 22 Molar distribution of cerium-zirconium oxide: Ce 0.50 Zr 0.45 Mn 0.05 O 1.99 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out precipitation reaction, the precipitation temperature is 0°C, the pH value during the precipitation is controlled to 9±0.2, and the pH value at the end of the precipitation is 11. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 450°C for 18 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.50 Zr 0.45 Mn 0.05 O 1.99 The molar distribution of Mn(NO 3 ) 2The molten salt liquid is mixed and manufactured at a certain volume, and the appropriate amount of Mn(NO 3 ) 2 The molten salt liquid was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 600°C for 0.5 hours, and then roasted at 950°C for 3 hours to obtain a cerium-zirconium composite oxide, which contains Mn element in the grain boundaries and on the surface and exists in the form of oxide. The total pore volume of the cerium-zirconium composite oxide was 0.404 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.206 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 50.3 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 35.2 m 2 / g.

[0074] Example 23 Molar distribution of cerium-zirconium oxide: Ce 0.40 Zr 0.45 S 0.10 Hf 0.02 Sr 0.03 O 1.98 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture is mixed with 3.0 mol / L aqueous ammonia solution to carry out precipitation reaction, the precipitation temperature is 30°C, the pH value during the precipitation is controlled to 9.0±0.2, and the pH value at the end of the precipitation is 10. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 650°C for 10 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.40 Zr 0.45 S 0.10 Hf 0.02 Sr 0.03 O 1.98 Ethyl orthosilicate with a total metal ion concentration of 1.6 mol / L, Sr(NO 3 ) 2 and HfO(NO 3) 2 A fixed volume of the mixed solution was prepared, and ethyl orthosilicate, Sr(NO 3 ) 2 , HfO(NO 3 ) 2 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, heat-treated at 350°C for 7 hours, and then roasted at 800°C for 5 hours to obtain a cerium-zirconium composite oxide, containing Si, Sr, and Hf elements at the grain boundaries and on the surface, all of which existed in the form of oxides. The cerium-zirconium composite oxide had a total pore volume of 0.467 mL / g, and a total pore volume of 0.229 mL / g after high-temperature aging at 1000°C for 10 hours. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 54.9 m. 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 37.3 m 2 / g.

[0075] (Example 24) Molar distribution of cerium-zirconium oxide: Ce 0.333 Zr 0.581 La 0.044 Pr 0.042 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out precipitation reaction, the precipitation temperature is 60°C, the pH value during the precipitation is controlled to 10±0.2, and the pH value at the end of the precipitation is 11. The precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 750°C for 6 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.333 Zr 0.581 La 0.044 Pr 0.042 O 1.98 The molar distribution of La(NO) with a total metal ion concentration of 1.0 mol / L 3 ) 3 , Pr(NO 3 )3 A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Pr(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 250°C for 4 hours, further heated to 400°C and heat-treated for 5 hours, and then roasted at 800°C for 6 hours to obtain a cerium-zirconium composite oxide, in which La and Pr were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.551 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.279 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 57.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 41.1 m 2 / g.

[0076] (Example 25) Molar distribution of cerium-zirconium oxide: Ce 0.373 Zr 0.520 La 0.044 Y 0.063 O 1.98 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 , La(NO 3 ) 3 A mixture of 250 mL of La (50% of the total amount of La required) was mixed and prepared, and the mixture was mixed with 3.0 mol / L aqueous ammonia solution to cause a precipitation reaction. The precipitation temperature was 30°C, the pH value during the precipitation was 9-12, and the pH value at the end of the precipitation was 9. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor. The precursor was then dried at 110°C for 10 hours and roasted at 700°C for 8 hours to obtain a cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.373 Zr 0.520 La 0.044 Y 0.063 O 1.98The molar distribution of La(NO) with a total metal ion concentration of 1.0 mol / L 3 ) 3 (50% of the total amount of La required), Y(NO 3 ) 3 A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 200°C for 5 hours, further heated to 450°C for 3 hours, and then roasted at 650°C for 5 hours, and further heated to 800°C for 3 hours to obtain a cerium-zirconium composite oxide, in which La and Y were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.501 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.254 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 56.3 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 38.4 m 2 / g.

[0077] (Example 26) Molar distribution of cerium-zirconium oxide: Ce 0.380 Zr 0.531 La 0.072 Pr 0.017 O 1.98 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out a precipitation reaction, the precipitation temperature is 30°C, the pH value during the precipitation is 10-14, the pH value at the end of the precipitation is 10.5, and the desired LaCl 3The solution was subjected to a second precipitation reaction with a sodium hydroxide solution, and the pH value at the end of the precipitation was 10.5. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 750°C for 5 hours to obtain a core-shell structured cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.380 Zr 0.531 La 0.072 Pr 0.017 O 1.98 The molar distribution of Pr(NO 3 ) 3 A fixed volume of solution was prepared and Pr(NO 3 ) 3 The solution was mixed uniformly with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 200°C for 5 hours, further heated to 450°C for 3 hours, and then roasted at 800°C for 3 hours to obtain a cerium-zirconium composite oxide with a core-shell structure, in which the shell was rich in praseodymium oxide and La and Pr were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.556 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.287 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 59.5 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 42.1 m 2 / g.

[0078] Example 27 Molar distribution of cerium-zirconium oxide: Ce 0.421 Zr 0.470 La 0.045 Y 0.064 O 1.97 CeCl with a total metal ion molar concentration of 1.0 mol / L 3 , ZrOCl 2The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out precipitation reaction, the precipitation temperature is 60°C, the pH value during the precipitation process is controlled to 5-11, the pH value is adjusted twice to carry out stepwise precipitation, the pH value is first adjusted to 5 to precipitate zirconium ions, and the pH value is gradually adjusted to 11 to precipitate cerium ions, the pH value at the end of the precipitation is 11, the precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 750°C for 6 hours to obtain a gradient distribution cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.421 Zr 0.470 La 0.045 Y 0.064 O 1.97 The total metal ion concentration of La(NO 3 ) 3 , Y(NO 3 ) 3 A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 150°C for 8 hours, further heated to 400°C for 5 hours, and then roasted at 800°C for 5 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had an element gradient distribution structure, and the exterior was rich in cerium oxide, lanthanum oxide, and yttrium oxide, and La and Y were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.597mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.295mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 62.8m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 43.1 m 2 / g.

[0079] (Example 28) Molar distribution of cerium-zirconium oxide: Ce 0.239 Zr 0.703 La 0.017 Nd 0.041 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out a precipitation reaction, the precipitation temperature is 80°C, and the pH value during the precipitation process is controlled to 9-11. Two-stage precipitation is carried out, the pH value is first adjusted to 5 to precipitate zirconium ions, and after aging for 1 hour, the pH value is further gradually adjusted to 11 to precipitate cerium ions. The pH value at the end of the precipitation is 11. The precipitate is subjected to post-treatment such as filtration and washing to obtain a precursor, which is then dried at 110°C for 10 hours and roasted at 600°C for 8 hours to obtain a core-shell structured cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.239 Zr 0.703 La 0.017 Nd 0.041 O 1.98 The total metal ion concentration of La(NO 3 ) 3 , Nd(NO 3 ) 3 A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Nd(NO 3 ) 3The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 250°C for 4 hours, further heated to 300°C for 5 hours, and then roasted at 600°C for 6 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had a core-shell structure, the exterior was rich in lanthanum oxide and neodymium oxide, and La and Nd were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.558 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.289 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 60.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 42.6 m 2 / g.

[0080] (Example 29) Molar distribution of cerium-zirconium oxide: Ce 0.330 Zr 0.576 La 0.035 Nd 0.034 Y 0.025 O 1.98 CeCl with a total metal ion molar concentration of 1.2 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out precipitation reaction, the precipitation temperature is 60°C, the pH value during the precipitation is controlled to 5-10, the pH value is adjusted twice to carry out stepwise precipitation, the pH value is first adjusted to 5 to precipitate zirconium ions, and the pH value is gradually adjusted to 10 to precipitate cerium ions, the pH value at the end of the precipitation is 10, the precipitate is filtered, washed and other post-treatments are carried out to obtain a precursor, which is dried at 110°C for 10 hours and roasted at 750°C for 6 hours to obtain a gradient distribution cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.330 Zr 0.576 La 0.035 Nd 0.034 Y 0.025 O 1.98The total metal ion concentration is 1.2 mol / L La(NO 3 ) 3 , Nd(NO 3 ) 3 , Y(NO 3 ) 3 A fixed volume of mixed solution was prepared and La(NO 3 ) 3 , Nd(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, and after drying, the mixture was heat-treated at 200°C for 6 hours, further heated to 400°C for 5 hours, and then roasted at 800°C for 5 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had an element gradient distribution structure, and the exterior was rich in lanthanum oxide, neodymium oxide, and yttrium oxide, and La, Nd, and Y were present in the form of oxides at the grain boundary and surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.571 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.299 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 62.8 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 43.1 m 2 / g.

[0081] (Example 30) Molar distribution of cerium-zirconium oxide: Ce 0.184 Zr 0.642 La 0.028 Y 0.146 O 1.98 CeCl with a total metal ion molar concentration of 0.7 mol / L 3 , ZrOCl 2 , Y.C.L. 3A mixture of 250 mL of (Y is 50%) was mixed and prepared, and the mixture was mixed with 2.5 mol / L sodium hydroxide solution to carry out a precipitation reaction. The precipitation temperature was 40°C, and the pH value during the precipitation process was controlled to be 5 to 11. The pH value was adjusted twice to carry out stepwise precipitation. First, the pH value was adjusted to 5 to precipitate zirconium ions, and then the pH value was gradually adjusted to 11 to precipitate cerium ions and yttrium ions. The pH value at the end of the precipitation was 11. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor. The precursor was dried at 110°C for 10 hours and roasted at 800°C for 5 hours to obtain a cerium-zirconium-containing oxide with a gradient distribution. Cerium-zirconium oxide (Ce) 0.184 Zr 0.642 La 0.028 Y 0.146 O 1.98 The molar distribution of La(NO) with a total metal ion concentration of 1.0 mol / L 3 ) 3 , Y(NO 3 ) 3 A mixture of La(NO 3 ) 3 , Y(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, and after drying, the mixture was heat-treated at 250°C for 4 hours, further heated to 450°C for 1 hour, and then roasted at 700°C for 4 hours, and further heated to 800°C for 3 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had an element gradient distribution structure, and the exterior was rich in lanthanum oxide and yttrium oxide, both on the exterior and interior, and La and Y were present in the form of oxides on the grain boundaries and surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.599mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.301mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 63.1m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 43.4 m 2 / g.

[0082] (Example 31) Molar distribution of cerium-zirconium oxide: Ce 0.326 Zr 0.569 La 0.043 Y 0.062 O 1.98 CeCl with a total metal ion molar concentration of 0.8 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out a precipitation reaction, the precipitation temperature is 60°C, the pH value during the precipitation process is controlled to 10-14, the final pH is 10, and the desired LaCl is obtained. 3 The solution was subjected to a second precipitation reaction with a sodium hydroxide solution, and the pH value at the end of the precipitation was 10. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 750°C for 6 hours to obtain a core-shell structured cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.326 Zr 0.569 La 0.043 Y 0.062 O 1.98 The molar distribution of Y(NO) with a total metal ion concentration of 1.5 mol / L 3 ) 3 A fixed volume of the solution was mixed and prepared, and Y(NO 3 ) 3 The solution was mixed uniformly with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 350°C for 3 hours, further heated to 400°C for 5 hours, and then roasted at 800°C for 5 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had a core-shell structure, the exterior was rich in lanthanum oxide and yttrium oxide, and La and Y were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.573 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.288 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 60.3 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 42.3 m 2 / g.

[0083] Example 32 Molar distribution of cerium-zirconium oxide: Ce 0.156 Zr 0.763 La 0.041 Nd 0.040 O 1.98 CeCl with a total metal ion molar concentration of 1.0 mol / L 3 , ZrOCl 2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out a precipitation reaction, the precipitation temperature is 60°C, the pH value during the precipitation process is controlled to 10-14, the final pH is 11, and the desired LaCl is obtained. 3 The second-stage precipitation reaction was carried out with the solution and a sodium hydroxide solution, and the pH value at the end of the precipitation was 11. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 850°C for 4 hours to obtain a core-shell structured cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.156 Zr 0.763 La 0.041 Nd 0.040 O 1.98 The molar distribution of Nd(NO 3 ) 3 A fixed volume of solution was prepared and Nd(NO 3 ) 3The solution was mixed uniformly with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 250°C for 4 hours, then heated to 300°C for 5 hours, and then roasted at 850°C for 4 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had a core-shell structure, the exterior was rich in neodymium oxide and lanthanum oxide, and La and Nd were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.598 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.298 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 60.9 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 42.9 m 2 / g.

[0084] (Example 33) Molar distribution of cerium-zirconium oxide: Ce 0.163 Zr 0.781 La 0.016 Nd 0.040 O 1.98 The total metal ion molar concentration of Ce(NO 3 ) 3 , ZrO(NO 3 ) 2 , Nd(NO 3 ) 3 A mixture containing 250 mL of cerium ions (50% Nd) was mixed and prepared, and the mixture was mixed with 3.0 mol / L aqueous ammonia solution to cause a precipitation reaction. The precipitation temperature was 35°C, and the pH value during the precipitation process was controlled to 5-10.5. The pH value was adjusted twice to cause stepwise precipitation. First, the pH value was adjusted to 5 to precipitate zirconium ions, and then the pH value was gradually adjusted to 10.5 to precipitate cerium ions and neodymium ions. The pH value at the end of the precipitation was 10.5. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor. The precursor was dried at 110°C for 10 hours and roasted at 600°C for 12 hours to obtain a gradient distribution cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.163 Zr 0.781 La0.016 Nd 0.040 O 1.98 The total metal ion concentration of La(NO 3 ) 3 , Nd(NO 3 ) 3 A mixed solution of La(NO 3 ) 3 , Nd(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, and after drying, the mixture was heat-treated at 250°C for 4 hours, further heated to 450°C and heat-treated for 1 hour, and then roasted at 800°C for 5 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had an element gradient distribution structure, and the exterior was rich in lanthanum oxide and neodymium oxide, both on the exterior and interior, and La and Nd were present in the form of oxides on the grain boundaries and surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.593 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.294 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 62.5 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 43.2 m 2 / g.

[0085] (Example 34) Molar distribution of cerium-zirconium oxide: Ce 0.523 Zr 0.365 La 0.046 Y 0.066 O 1.98 The total metal ion molar concentration of Ce(NO 3 ) 3 (Ce is 50% by weight), ZrO(NO 3 ) 2 The mixture is mixed with 3 mol / L aqueous ammonia solution to carry out a precipitation reaction. The precipitation temperature is 30°C, the pH value during the precipitation process is controlled to 9-11, the final pH is 11, and the desired Y(NO 3 ) 3、 Ce(NO3 ) 3 A second precipitation reaction was carried out using a mixed solution (containing 50% Ce) and a sodium hydroxide solution, the pH value at the end of the precipitation was 10, and the precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor. The precursor was then dried at 110°C for 10 hours and roasted at 700°C for 10 hours to obtain a core-shell structured cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.523 Zr 0.365 La 0.046 Y 0.066 O 1.98 The total metal ion concentration of La(NO 3 ) 3 A fixed volume of solution was prepared and La(NO 3 ) 3 The solution was mixed uniformly with the cerium-zirconium-containing oxide obtained above, and after drying, the mixture was heat-treated at 200°C for 4 hours, then heated to 350°C for 4 hours, and then heated to 600°C for 5 hours, and then heated to 850°C for 3 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had a core-shell structure, and the exterior was rich in cerium oxide, lanthanum oxide, and yttrium oxide, and La and Y were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.599mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.311mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 63.2m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 43.5 m 2 / g.

[0086] Example 35 Molar distribution of cerium-zirconium oxide: Ce 0.48 Zr 0.34 La 0.04 Mg 0.06 Mn 0.08 O 1.98 CeCl with a total metal ion molar concentration of 1.5 mol / L 3 , ZrOCl2 The mixture is mixed with 2.5 mol / L sodium hydroxide solution to carry out a precipitation reaction. The precipitation temperature is 35°C, the pH value during the precipitation process is controlled to 9-11, the final pH is 11, and the desired MgCl 3 The solution was subjected to a second precipitation reaction with a sodium hydroxide solution, and the pH value at the end of the precipitation was 10.5. The precipitate was subjected to post-treatment such as filtration and washing to obtain a precursor, which was then dried at 110°C for 10 hours and roasted at 800°C for 8 hours to obtain a core-shell structured cerium-zirconium-containing oxide. Cerium-zirconium oxide (Ce) 0.48 Zr 0.34 La 0.04 Mg 0.06 Mn 0.08 O 1.98 The total metal ion concentration of La(NO 3 ) 3 , Mn(NO 3 ) 3 The mixed solution was prepared by mixing a certain volume of La(NO 3 ) 3 , Mn(NO 3 ) 3 The mixed solution was uniformly mixed with the cerium-zirconium-containing oxide obtained above, dried, and then heat-treated at 100°C for 8 hours, further heated to 400°C for 3 hours, and then roasted at 700°C for 6 hours to obtain a cerium-zirconium composite oxide. The cerium-zirconium composite oxide had a core-shell structure, the exterior was rich in manganese oxide and lanthanum oxide, and La, Mn, and Mg were present in the form of oxides at the grain boundaries and on the surface of the cerium-zirconium composite oxide. The total pore volume of the cerium-zirconium composite oxide was 0.580 mL / g, and the total pore volume after high-temperature aging at 1000°C for 10 hours was 0.289 mL / g. The specific surface area of ​​the cerium-zirconium composite oxide after high-temperature aging at 1000°C for 10 hours was 61.2 m 2 / g, and the specific surface area after high temperature aging at 1100°C for 4 hours is 42.8 m 2 / g.

[0087] From the data shown in the above examples, it can be seen that the total pore volume of the cerium zirconium composite oxide obtained by adopting the manufacturing method of the embodiment of the present invention and the total pore volume after high-temperature aging at 1000°C for 10 hours are obviously higher than the total pore volume of the cerium zirconium composite oxide obtained by adopting the manufacturing method of the comparative example. The cerium zirconium composite oxide obtained by adopting the manufacturing method of the embodiment of the present invention has a specific surface area after high-temperature aging at 1000°C for 10 hours and a specific surface area after high-temperature aging at 1100°C for 4 hours that are both higher than the specific surface area of ​​the cerium zirconium composite oxide obtained by adopting the manufacturing method of the comparative example. The cerium zirconium composite oxide obtained by adopting the manufacturing method of the embodiment of the present invention can obtain excellent high-temperature stability.

[0088] As described above, the present invention relates to a cerium zirconium composite oxide doped on the grain boundary and surface, its manufacturing method and use, and improves the high-temperature stability and catalytic application effect of the cerium zirconium composite oxide. The cerium zirconium composite oxide provided by the present invention contains doping elements on its grain boundary and surface, and the doping elements are located on its grain boundary and surface, so that the number of defects and vacancies of the cerium zirconium composite oxide is increased, the oxygen transfer ability is enhanced, and the high-temperature stability performance is good. Moreover, the cerium zirconium composite oxide can inhibit the migration, aggregation and growth of precious metal particles, and enhance the high-temperature stability of precious metal catalysts, and can be applied in the fields of automobile exhaust gas purification, natural gas catalytic combustion, organic exhaust gas purification, and industrial flue gas denitrification treatment.

[0089] It should be understood that the above-mentioned specific embodiments of the present invention are only used to exemplarily explain or interpret the principles of the present invention, and are not intended to limit the present invention. Therefore, any modifications, equivalent replacements, improvements, etc. made without departing from the spirit and scope of the present invention shall be included in the scope of protection of the present invention. Furthermore, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.

Claims

1. A cerium zirconium composite oxide doped at grain boundaries and surfaces, the chemical formula of the cerium zirconium composite oxide being: Ce x Zr 1-x-y M y O 2-α D δ where: M is a cationic doping element and D is an anionic doping element; A cerium-zirconium composite oxide doped at grain boundaries and on a surface thereof, characterized in that 0.1≦x≦0.9, 0<y≦0.2, 0≦α≦0.1, and 0≦δ≦0.

1.

2. The grain boundaries and surface of the cerium-zirconium composite oxide according to claim 1, characterized in that the grain boundaries and surface of the cerium-zirconium composite oxide contain one or more of an oxide of a doping element M, or an oxide of a doping element M and a nitrogen-containing compound formed by M and D, a fluoride, a phosphate, and a sulfate.

3. The cerium-zirconium composite oxide doped at the grain boundaries and on the surface according to claim 1 or 2, characterized in that the doping element M is one or a combination of one or more of a rare earth element other than cerium, a transition metal element, an alkaline earth metal element, Al, and Si, and the doping element D is one or a combination of one or more of N, S, F, and P.

4. The cerium zirconium composite oxide doped at the grain boundaries and on the surface according to claim 3, characterized in that the rare earth element is one or a combination of one or more of La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc, the transition metal element is one or a combination of one or more of Cu, Mn, Ni, Fe, Zn, Co, Ti, Hf, Cr, and W, and the alkaline earth metal element is one or a combination of one or more of Mg, Ca, Sr, and Ba.

5. The cerium zirconium composite oxide doped at the grain boundaries and on the surface according to claim 4, characterized in that the cationic doping element M comprises one or a combination of one or more of La, Pr, Nd, Sm, Eu, Yb, Y, Sc, Cu, Mn, Hf, Fe, Co, Al, Si, Mg, Ba and Sr.

6. The cerium-zirconium composite oxide has a specific surface area of ​​50 m after being kept at 1000° C. for 10 hours. 2 / g, preferably 60m 2 / g, and the specific surface area after heating at 1100°C for 4 hours is 35 m 2 / g, preferably 40m 2 6. The cerium-zirconium composite oxide doped at the grain boundaries and on the surface according to claim 1, wherein the zirconium-cerium complex oxide has a surface roughness of 0.1 to 0.5 nm, and the surface roughness of the cerium-zirconium complex oxide is 0.1 to 0.5 nm.

7. The cerium zirconium composite oxide according to any one of claims 1 to 5, characterized in that the total pore volume of the cerium zirconium composite oxide is greater than 0.4 mL / g, and the total pore volume after being kept at 1000°C for 10 hours is greater than 0.2 mL / g.

8. The cerium zirconium composite oxide doped at the grain boundaries and on the surface according to any one of claims 1 to 7, characterized in that it has an element gradient distribution structure or a core-shell structure, preferably one or more of a structure in which the outer surface or shell is rich in cerium oxide, a structure in which the doping element M is rich on the outer surface, or a structure in which the doping element M is on the outer surface and / or in the interior.

9. Step S1: preparing aqueous solutions containing cerium ions and zirconium ions in a stoichiometric ratio required for the product, mixing them to obtain a mixed solution, subjecting the mixed solution to a one-stage or two-stage precipitation reaction with a basic substance in a reactor, filtering, washing, drying and roasting the resulting precipitate to obtain a cerium-zirconium-containing oxide; and step S2 of mixing the cerium-zirconium-containing oxide obtained in step S1 with liquid salts of doping elements M and D, drying the mixture, subjecting the mixture to one or two heat treatments, and further subjecting the mixture to one or two roastings to obtain a cerium-zirconium composite oxide doped at the grain boundaries and on the surface.

10. 10. The method of claim 9, wherein the aqueous solution containing zirconium ions in step S1 comprises one or a combination of one or more aqueous solutions of zirconium oxychloride, zirconium oxynitrate, zirconium sulfate, zirconium acetate, and zirconium citrate.

11. 10. The method of claim 9, wherein the aqueous solution containing cerium ions in step S1 comprises one or a combination of one or more aqueous solutions of cerium chloride, cerium nitrate, cerium sulfate, cerium acetate, and cerium citrate.

12. 10. The method according to claim 9, characterized in that the basic substance comprises at least one of magnesium hydrogen carbonate, urea and hydroxide, carbonate or hydrogen carbonate of at least one of the elements ammonium, sodium and potassium, preferably at least one of sodium hydroxide, urea, aqueous ammonia and ammonium hydrogen carbonate.

13. The method according to claim 9, wherein the pH value during the precipitation process in step S1 is controlled to be 4.5-14, preferably 5-11, the pH value at the end of the precipitation is controlled to be 8-13, preferably 9-11, and the reaction temperature during the precipitation process is 0-120°C, preferably 20-80°C.

14. 10. The method of claim 9, wherein the liquid salts of doping elements M comprise one or a combination of one or more of the following: chlorides, nitrates, sulfates, acetates, citrates, amino acid salts and molten salts or aqueous solutions of organosilicon compounds.

15. 10. The method according to claim 9, wherein the doping element M is added in one or two steps in steps S1 and S2.

16. 10. The method according to claim 9, wherein the doping element D is added in one or two steps in steps S1 and S2.

17. 17. The method according to claim 16, characterized in that the doping element D is added in the form of one or a combination of one or more of the following: nitrates, fluorides, phosphates and sulfates.

18. The method according to claim 9, wherein the roasting temperature in step S1 is 500-1050°C and the time is 1-24h, preferably the roasting temperature is 600-950°C and the time is 3-12h.

19. The method according to claim 9, wherein the heat treatment temperature in step S2 is 100-600° C. and the time is 0.5-24 h, preferably the heat treatment temperature is 150-450° C. and the time is 1-12 h.

20. The method according to claim 9, wherein the roasting temperature in step S2 is 500-1050°C and the roasting time is 1-24h, preferably the roasting temperature is 600-950°C and the roasting time is 3-12h.

21. A catalyst, characterized in that it is produced by employing the grain boundary and surface doped cerium zirconium composite oxide according to any one of claims 1 to 8.

22. The use of the catalyst according to claim 21 in the fields of automobile exhaust gas purification, natural gas catalytic combustion, organic exhaust gas purification and industrial flue gas denitrification treatment.

Citation Information

Patent Citations

  • Controllable dual-porous Ce / Zr composite oxide, and preparation method and application thereof

    CN109529801A

  • Exhaust gas purification catalyst and production method thereof

    JP2012245452A

  • Catalyst containing cerium oxide and copper and production method thereof

    JP2015208692A

  • Cerium and zirconium based mixed oxides

    JP2019518693A

  • Oxygen storage material and method for producing the same

    JP2020059630A